O convívio da diferença: práticas biopolíticas no jogo de dentro e no jogo de fora - Rios, Livia Sernache (2018)
This research investigates the "capoeira" and explores it as a form of communication with the Other. We place "capoeira" as a practice that exercises the ability to cooperate, understanding it as a cognitive action that invites us to reconfigure our interpretations about the world. The understanding of "capoeira" proposed by this research deals with the context in which we live, trying to understand the presence of the new cognitive habits that lead us today. With it, we identify the power relations engendered by a neoliberal reason, which defines our current modes of existence, focusing on new forms of communication in which life practices (on/offline) (KATZ, 2015) are increasingly dissociated. Based on the assumption that communication can only occur with the Other, it is possible to formulate the hypothesis, supported by Sennett (2008, 2012) - which says that "to do" is "to think" - about capoeira as a way to contribute to the flourishing of a more cooperative life, since it operates in the sense of something that can only be constructed together with that Other - not in a two-way relationship, but in a pair of hands and eyes, which allow us to learn with the difference. The game inside (the "capoeira") and the outside game (of life) coexist in the same sea created by the current stage of capitalism; and the objective here is to demonstrate that there are specificities, in the rules of "capoeira", that can help us to swim in these waters. The "capoeira" insists on practicing the conviviality, and the Bodymedia Theory (KATZ and GREINER) explains us that the relationship with the Other and with the environment always affects everyone involved. The theoretical basis also includes, among others, Sennett (2008, 2012) and Tomasello (2004), to consolidate the proposal of collaboration as an evolutionary trait; and Dardot and Laval (2016, 2017), to situate the advances of neoliberalism. Dardot and Laval (2017) also help us to think about the ordinary. This research adds bibliographic review and listening in the conviviality with masters and practitioners of "capoeira", and arises from the urgency of collaborating to build a life based on cooperation